A review of the theoretical and numerical approaches to modeling skyglow: Iterative approach to RTE, MSOS, and two-stream approximation. (September 2016) - Kocifaj, Miroslav
Abstract: The study of diffuse light of a night sky is undergoing a renaissance due to the development of inexpensive high performance computers which can significantly reduce the time needed for accurate numerical simulations. Apart from targeted field campaigns, numerical modeling appears to be one of the most attractive and powerful approaches for predicting the diffuse light of a night sky. However, computer-aided simulation of night-sky radiances over any territory and under arbitrary conditions is a complex problem that is difficult to solve. This study addresses three concepts for modeling the artificial light propagation through a turbid stratified atmosphere. Specifically, these are two-stream approximation, iterative approach to Radiative Transfer Equation (RTE) and Method of Successive Orders of Scattering (MSOS). The principles of the methods, their strengths and weaknesses are reviewed with respect to their implications for night-light modeling in different environments. Highlights: Three methods for modeling nightsky radiance are reviewed. The two-stream approximation allows for rapid calculation of radiative fluxes. The above approach is convenient for modeling large uniformly emitting areas. SOS is applicable to heterogeneous deployment of well-separated cities or towns. MSOS is generally CPU less-intensive than traditional 3D RTE.